Mesiodistal angulation of posterior teeth in orthodontic patients with different facial growth patterns - Mohammadreza Badiee; Asghar Ebadifar; Sanaz Sajedi (Tabriz University of Medical Sciences, 2019)
Background. Mesiodistal and buccolingual angulations of teeth are variable in different malocclusion classes. This study aimed to assess the mesiodistal angulation of posterior teeth in orthodontic patients with vertical, normal, and horizontal facial growth patterns. Methods. This descriptive, cross-sectional study evaluated 150 lateral cephalograms of orthodontic patients. According to cephalometric analysis, facial growth patterns were divided into three groups of normal, horizontal, and vertical (n=50). The angulation of maxillary and mandibular posterior teeth was then measured. Data were analyzed using SPSS 22. Results. The results showed an increase in the mean angle of maxillary and mandibular posterior teeth relative to palatal and mandibular planes in patients with a vertical facial growth pattern. Conversely, their angulation decreased relative to the bisected occlusal plane (BOP). The angulation of posterior teeth decreased relative to palatal and mandibular planes and increased relative to the occlusal plane with an increase in overbite. The mean angle of all maxillary teeth relative to the palatal plane was significantly greater in open bite patients compared to normal and deep bite patients. This value in patients with normal bite was significantly greater than that in deep bite patients (P<0.05). Conclusion. The current results revealed that in patients with a vertical growth pattern, all the posterior teeth had a forward inclination. Conversely, in patients with a horizontal growth pattern, the teeth had a backward inclination.